Functional characterization of recombinant bromelain - Amid, Azura; Bala, Muntari; Mohd. Salleh, Hamzah (2015)
Stem bromelain is a plant protease with a number of industrial and therapeutic applications. This study investigated the functional properties of commercial bromelain and recombinant bromelain (expressed in E. coli BL 21-AI). In vitro cytotoxicity assays were conducted to evaluate the effect of both bromelains on tumour cell lines (murine melanoma and breast cancer MCF-7) and normal cells (Vero and Chinese hamster ovary) using Sulforhodamine B and MTT tests. Anti-inflammatory activities of the enzymes were also assessed on murine macrophage cell lines using Griess reagents and ELISA test. The beef tenderizing effects of both bromelains and in-situ localization of the recombinant bromelain were analysed using Transmission Electron Microscopy. The results obtained revealed that both bromelains were more cytotoxic to tumour cell lines (IC50 values ≈ 0.16-0.23mg/mL) than normal cell lines (IC50 values ≈ 0.27-0.51mg/mL). Moreover, the two enzymes had effectively inhibited the pro-inflammatory mediators’ production and thus, had good anti-inflammatory activity. Both enzymes were found to have comparative anti-cancer and anti-inflammatory properties. The expression of recombinant enzyme was discovered to occur in the cytoplasm of E. coli BL 21-AI and the purified enzyme efficiently degraded both actin and myosin of fresh beef. Hence, it served as a good meat tenderizer.